2023
DOI: 10.3389/fpsyg.2022.1070975
|View full text |Cite
|
Sign up to set email alerts
|

The gold-standard treatment for social anxiety disorder: A roadmap for the future

Abstract: Exposure therapy (ET), which follows the Pavlovian extinction model, is regarded as the gold-standard treatment for social anxiety disorder (SAD). The prospect of virtual reality in lieu of a traditional laboratory setting for the treatment of SAD has not been rigorously explored. The aim of the review was to summarize, find gaps in the current literature, and formulate future research direction by identifying two broad research questions: the comparative efficacy between in vivo ET and virtual reality exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For decades, experimental researchers have voiced concerns about the translational limitations of experimental paradigms that model extinction learning (Rachman, 1977;Poulton and Menzies, 2002;Mineka and Zinbarg, 2006;De Houwer, 2020) and avoidance (Krypotos et al, 2015). Echoing these concerns in the domain of clinical fear reduction, recent reviews have advised experimental researchers to "mind the gap" between fear reduction through extinction in the laboratory and the treatment of fear through exposure in the clinic (Carpenter et al, 2019) and urged the development of refined therapeutic models (Chowdhury and Khandoker, 2022;Nihei et al, 2023). Notably, Craske et al (2008) suggested that, in addition to extinction learning, investigators should consider "other clinically relevant cognitiveemotional processes" that contribute to the beneficial effects of exposure therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, experimental researchers have voiced concerns about the translational limitations of experimental paradigms that model extinction learning (Rachman, 1977;Poulton and Menzies, 2002;Mineka and Zinbarg, 2006;De Houwer, 2020) and avoidance (Krypotos et al, 2015). Echoing these concerns in the domain of clinical fear reduction, recent reviews have advised experimental researchers to "mind the gap" between fear reduction through extinction in the laboratory and the treatment of fear through exposure in the clinic (Carpenter et al, 2019) and urged the development of refined therapeutic models (Chowdhury and Khandoker, 2022;Nihei et al, 2023). Notably, Craske et al (2008) suggested that, in addition to extinction learning, investigators should consider "other clinically relevant cognitiveemotional processes" that contribute to the beneficial effects of exposure therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Generalized SAD differs from the performance-only subtype in that it has a higher number of feared social situations and involves more interactive social situations than talking to an audience. The effectiveness of using in virtuo exposure in the treatment of performance-only SAD has been demonstrated in several studies [ 24 , 27 , 31 , 32 , 33 ]. Clinical trials have also shown that in virtuo exposure using real-time 3D rendering technology is just as effective as traditional in vivo exposure when treating patients with SAD that have broader social fears than only performance [ 14 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%